Functional Outcome Assessment in Neglected Proximal Interphalangeal Joint Dislocation Managed by Dynamic Suzuki Frame External Fixator - Pranav Kothiyal; Kunal Vij; Pritish Gautam; Yogesh Ahuja (Journal of Orthopedics, Traumatology and Rehabilitation)
Aims and Objectives: This research article evaluates the functional outcomes of patients treated for neglected proximal interphalangeal (PIP) joint dislocations using the dynamic Suzuki frame external fixator. Material and Methods: Patients with neglected interphalangeal joint dislocations were managed initially by distractor application followed by dynamic suzuki frome application and were then followed up for improvement in hand functions. The study employs the Visual Analog Scale score, range of motion at interphalangeal joints, and the Sollerman Hand Function Test to quantify hand functionality pre and post treatment. Results: Indicate significant improvements in hand function and patient satisfaction, underscoring the efficacy of this intervention for neglected PIP joint dislocations. Conclusion: Dynamic suzuki frame can be considered as a effective and promising option for management of neglected Interphalangeal joint dislocations.